Nickel-catalysed enantioselective arylative cyclisations - Clarke, Christopher (2019)
Enantioselective Nickel-catalysed anti-Carbometallative Cyclisations of Alkynyl Electrophiles Enabled by Reversible Alkenylnickel E/Z Isomerisation. Highly enantioselective anti-carbometallations of alkynes bearing tethered ketones is described using a Ni(II) salt and a commercially available chiral phosphinooxazoline ligand. Due to the syn-selective nature of alkyne-migratory insertion, many examples of carbometallative processes giving the cyclised syn-products have been reported, however, anti¬-carbometallative processes are rare. The mechanism of this anti-carbometallation is thought to occur via an alkenylnickel E/Z-isomerisation of the organometallic species formed after initial alkyne migratory insertion. Although a number of examples of such isomerisaions have been reported, the utilisation of the phenomina in ring-forming reactions to give anti-carbometallation products is much less well explored. Further reaction development for the nickel-catalysed anti-carbometallative cyclisations of alkynyl electrophiles has allowed for the synthesis of enantioenriched cyclopentenones using malonates as electrophiles. The use of the trifloroethanol leaving group on a malonate electrophile is important for efficient reactivity and allows the previously unreactive ester electrophile to be used. However, inorder to obtain high enantioselectivities and aryl group at the quaternaty centre of the substrate is required.